The futures of European capitalism - Schmidt, Vivien A. (New York, 2002)
"In this path-breaking book, the author argues that European countries' political-economic policies, practices, and discourses have changed profoundly in response to globalization and Europeanization, but they have not converged. Although national policies may now be more similar, especially where they follow from common European policies, they are not the same. National practices, although moving in the same general direction toward greater market orientation, continue to be differentiable into not just one or even two but three varieties of capitalism. And national discourses that generate and legitimate changes in policies and practices not only remain distinct, they matter. The book is a tour de force which combines sophisticated theoretical insights and innovative methods to show that European countries generally, but in particular Britain, France, and Germany , have had very different experiences of economic adjustment, and will continue to do so into the future. "